KINERJA ANGKUTAN UMUM OPLET (EKSISTING) DAN URGENSI OPERASIONALISASI ANGKUTAN UMUM BERBASIS BIS YANG MEMENUHI SPM DI KOTA PONTIANAK - Said, Said (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The quality of performance of public transport of oplet operation keep on decline, in comfort aspects, safety aspects and also expansion of service coverage. Based on BPS data, in 2012, population of Pontianak city is 565,856 inhabitants, while the number of private vehicles 43,182 vehicles; or 1private vehicles per 1  inhabitants The aim of this study is to show that without restrictions of private vehicle ownership, restrictions on the use of private vehicle, and support to the provision of public transport services then the impact is service level of road network which becomes very low. This condition can be observed in some roads that faced severe congestion or have a high DS value. The lack of attention that the city government who should carry out the implementation of the Standar Pelayanan Minimal (SPM) further exacerbate the performance of the public transport network of transportation in the city of Pontianak, which is indicated by the value of total load factor of 0.26.